SENGKETA AKIBAT PEMUTUSAN KERJA SAMA ANTARA PT. SARANA INVESTAMA MANGGABAR DENGAN PROVINSI NUSA TENGGARA TIMUR - Keban, Angelina Bernadina Linojawa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Basically, humans are social creatures (zoon politicon) who interact with each other. The increasingly rapid interaction of the community often leads people to bind themselves with other communities, resulting in making an agreement. Agreement is one of the legal studies that is always evolving, along with the development of society. Onong Uchana Effendy in his book Communication Science Theory and Practice reveals that "Humans as social beings need interaction with each other to share feelings, exchange thoughts and desires, either directly or indirectly, verbally and nonverbally. This is naturally ingrained in every individual, and is naturally done from birth. After the occurrence of an agreement between the two parties then an agreement appears between them. From this agreement, there was cooperation between the two parties, namely PT. Sarana Investama Manggabar and East Nusa Tenggara Province. In the cooperation that is built between the two parties who work together, problems often occur, namely defaults between them or it can be said that the employment relationship is unilaterally terminated